Unfinished business in agricultural trade liberalisation - Glauber, Joseph W. (2016)
Unfinished Business discusses unresolved issues in agricultural negotiations and proposes strategies for addressing discipline in domestic support and increasing market access. These recommendations come at an important time for the Cairns Group as we approach MC11 and continue to press forward with much-needed agricultural trade reform.